2011
DOI: 10.3349/ymj.2011.52.5.845
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Thrombocytopenia-Associated Multiple Organ Failure Using Red Blood Cell Parameters and a Volume/Hemoglobin Concentration Cytogram

Abstract: Thrombocytopenia-associated multiple organ failure (TAMOF) has a high mortality rate when not treated, and early detection of TAMOF is very important diagnostically and therapeutically. We describe herein our experience of early detection of TAMOF, using an automated hematology analyzer. From 498,390 inpatients, we selected 12 patients suspected of having peripheral schistocytosis, based on the results of red blood cell (RBC) parameters and a volume/hemoglobin concentration (V/HC) cytogram. We promptly evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 21 publications
1
26
1
1
Order By: Relevance
“…Monitoring of haemoglobin level, platelet counts, LDH, and peripheral blood smear schistocyte counts were also used as reliable therapeutic end points to monitor the effectiveness of TPE therapy ( P < .05). While LDH levels have not been shown to be a useful determinant of treatment duration in all studies, the red cell distribution width has consistently been found to be an excellent monitoring tool for the presence of schistocytes …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Monitoring of haemoglobin level, platelet counts, LDH, and peripheral blood smear schistocyte counts were also used as reliable therapeutic end points to monitor the effectiveness of TPE therapy ( P < .05). While LDH levels have not been shown to be a useful determinant of treatment duration in all studies, the red cell distribution width has consistently been found to be an excellent monitoring tool for the presence of schistocytes …”
Section: Discussionmentioning
confidence: 96%
“…While LDH levels have not been shown to be a useful determinant of treatment duration in all studies, 21 the red cell distribution width has consistently been found to be an excellent monitoring tool for the presence of schistocytes. 22 The management of TTP at academic centres in SA has been previously published. [4][5][6] In the absence of local guidelines, the management varies between centres.…”
Section: Discussionmentioning
confidence: 99%
“…The International Council for Standardization in Hematology (ICSH) Schistocyte Working Group recommended that the more than 1% schistocytes on a peripheral blood smear is an important criterion for identifying TMA [13]. Moreover, the occurrence of schistocytes in blood re ects a high risk of thrombocytopenia-associated multiple organ failure (TAMOF) [17]. Schistocytes indicate speci c characteristics of increased red cell distribution width (RDW) and hemoglobin distribution width (HDW), and microcytic hyperchromic red blood cells (RBCs) [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the occurrence of schistocytes in blood re ects a high risk of thrombocytopenia-associated multiple organ failure (TAMOF) [17]. Schistocytes indicate speci c characteristics of increased red cell distribution width (RDW) and hemoglobin distribution width (HDW), and microcytic hyperchromic red blood cells (RBCs) [15,17]. Based on the development and changes in the morphological characteristics of schistocytes, the TMA score was developed as a rapid, simple marker to screen for TAMOF in critically ill patients [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation